The Effect of Accounting Conservatism, Company Size and Good Corporate Governance on the Quality of Company Profits - Zuriani Ritonga; Lakharis Inuzula; Mulyadi Mulyadi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
Failure of financial reports to meet the information needs of report users. Profit, which should be an indicator for decision making, is not presented in accordance with actual facts about the company's economic condition, so the quality is doubtful. Profits that do not show true information about the company's performance will have an impact on the objectives to be achieved by the users of the report. This study aims to determine the effect of accounting conservatism, company size and good corporate governance on the quality of company earnings. The data used in this study is secondary data in the form of financial statements of non-financial institution companies from 2018 to 2022. This research uses descriptive statistical analysis. The results showed that Conservatism has a positive effect on earnings quality, the tcount value is 3.319 with a significance level of 0.003, company size and good corporate governance have no effect on earnings quality. This means the hypothesis is rejected. The coefficient of determination ((R2) shows the magnitude of the contribution of the independent variable to the dependent variable. 0.825 This means that 82.5% of the quality of company earnings is influenced by accounting conservatism, company size and good corporate governance, while the remaining 7.5% is influenced by other variables not examined.